2008
DOI: 10.1089/end.2007.0385
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Robot-Assisted NOTES Nephrectomy: Initial Report

Abstract: A robot-assisted NOTES nephrectomy was accomplished in a porcine model using the daVinci S robot. Additional testing on survival animals is necessary to further explore this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 24 publications
0
47
0
1
Order By: Relevance
“…The recognized benefits of the da Vinci Surgical System (Intuitive Surgical, Sunnyvale, CA, USA) over conventional laparoscopy include superior ergonomics, optical magnification of the operative field, enhanced surgeon dexterity, and precision of surgical manipulation [82]. Box et al first reported a hybrid NOTES robot-assisted nephrectomy in a porcine model with combined transvaginal and transcolonic access [83]. The authors pointed out that even if currently the robotic system offers many potential advantages, technical difficulties still need to be overcome, including robotic arm collisions, limited triangulation despite the EndoWrist (Intuitive Surgical, Sunnyvale, CA, USA) instruments, and counterintuitive camera angles.…”
Section: Lowmentioning
confidence: 99%
“…The recognized benefits of the da Vinci Surgical System (Intuitive Surgical, Sunnyvale, CA, USA) over conventional laparoscopy include superior ergonomics, optical magnification of the operative field, enhanced surgeon dexterity, and precision of surgical manipulation [82]. Box et al first reported a hybrid NOTES robot-assisted nephrectomy in a porcine model with combined transvaginal and transcolonic access [83]. The authors pointed out that even if currently the robotic system offers many potential advantages, technical difficulties still need to be overcome, including robotic arm collisions, limited triangulation despite the EndoWrist (Intuitive Surgical, Sunnyvale, CA, USA) instruments, and counterintuitive camera angles.…”
Section: Lowmentioning
confidence: 99%
“…Two segments (15)(16)(17)(18)(19)(20) cm) from the small bowel and one segment (20 cm) from the rectum were collected from adult pigs (50-60 kg). The pigs were cared for according to the "Guidelines for the Care and Use of Laboratory Animals" at the Takaramachi Campus of Kanazawa University.…”
Section: Transrectal Notes Modelmentioning
confidence: 99%
“…However, reports of robotic NOTES using the da Vinci Surgical system are rare as the surgical port is limited to the umbilicus, rectum, and vagina in such procedures [18,19]. Using the da Vinci Surgical system with transrectal robotic NOTES allows surgery that requires a high degree of freedom such as intraperitoneal suturing.…”
Section: Introductionmentioning
confidence: 99%
“…Single-incision laparoscopic surgery is a very exciting new modality in the field of minimal access surgery which works for further reducing the scars of standard laparoscopy and towards scarless surgery [1][2][3]. Scarless surgery is the Holy Grail of surgery [4].…”
Section: Introductionmentioning
confidence: 99%